THE INFLUENCE OF USING FINGER PUPPET IN TEACHING SELECTIVE LISTENING SKILL IN NARRATIVE TEXT AT EIGHT GRADE OF SMP PGRI KOTA CILEGON - Lionny Ansi Arivasari; Delsa Miranty; Welliam Hammer (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2018)
The objective of this research was to find out the influence of using finger puppet in teaching selective listening skill in narrative text at eight grade of SMP PGRI Kota Cilegon. The researcher used quantitative research by using true experimental design for conducting the research. The subject of this research used cluster random sampling, which consist of two classes. The experimental class was VIII A consist of 22 students and VIII B as control class with 23 students. The instrument of this research was test. The types of the instrument were pre-test and post-test that given to both class. Before giving pre-test and post-test, the researcher conducted try-out test in other class to know if the instrument that used in pre-test and post-test was valid and reliable as research instrument. In testing the hypothesis the researcher used t-test as formulas to find out the influence of using finger puppet in teaching selective listening skill in narrative text at eight grade of SMP PGRI Kota Cilegon. The result of this research, shown that by using finger puppet was 3,1739. It can be concluded that tcount ≥ ttable or 3,1739 ≥ 2,018.